The question of translation and translation studies - Asruddin Barori Tou (Journal of Modern Languages)
Over the centuries, translation as a phenomenon has been addressed in several fields of study: literary studies, cultural studies, linguistics, etc. In the last quarter of the 20th. century, scholars' continuous attempt and perseverance to establish a discipline gained momentum in the 19705, in which the designation translation studies was suggested and in its turn widely accepted. It is also claimed that its subsequent development as a separate discipline is a success story of the 1980s. Now, the subject has developed in many parts of the world, and there is a tendency for translation studies to emancipate itself as a discipline through a drastic separation from the other disciplines. While this tendency may be historically understandable, one may be led to a loss of contexts which is crucial to an understanding of the phenomena of translation. This paper will address questions that centre round the state of translation studies development as a discipline in its own right and contact with other discipline; and those that are associated with the notion of translation itself.